Psychometric properties of the reactive/proactive questionnaire (RPQ) and How I Think Questionaire (HIT) in Peruvian high school students - Rojas Zegarra, María Elena (2020)
The present study aimed to value the relationships between reactive/proactive aggression and cognitive distortion among adolescents from Arequipa City in Peru, for which it was necessary to realize a psychometric analysis of the tests used. Evaluated were 2,830 high school students (48.9% female and 51.1% male) aged between 13 and 19 years old, with the Reactive/Proactive Aggression Questionnaire and the How I Think Questionnaire. A psychometric analysis was performed to evaluate the validity and reliability of the instruments applied, as well as a correlation analysis to determine the relation between the variables. The psychometric results show a construct validity and reliability of the questionnaires, with adequate fit values and internal consistency; while the correlation analysis reveals that the reactive aggression is weakly related with cognitive distortions, and proactive aggression is moderately related to cognitive distortions. Propiedades psicométricas de los cuestionarios Reactive/Proactive Questionnaire (RPQ) y How I Think Questionaire (HIT) en estudiantes peruanos